A study of the peopling of Greenland using next generation sequencing of complete mitochondrial genomes. Issue 4 (24th August 2016) - Lopopolo, Maria; Børsting, Claus; Pereira, Vania; Morling, Niels
Abstract: Objectives: The Greenlandic population history is characterized by a number of migrations of people of various ethnicities. In this work, the analysis of the complete mtDNA genome aimed to contribute to the ongoing debate on the origin of current Greenlanders and, at the same time, to address the migration patterns in the Greenlandic population from a female inheritance demographic perspective. Methods: We investigated the maternal genetic variation in the Greenlandic population by sequencing the whole mtDNA genome in 127 Greenlandic individuals using the Illumina MiSeq ® platform. Results: All Greenlandic individuals belonged to the Inuit mtDNA lineages A2a, A2b1, and D4b1a2a1. No European haplogroup was found. Discussion: The mtDNA lineages seem to support the hypothesis that the Inuit in Greenland are descendants from the Thule migration. The results also reinforce the importance of isolation and genetic drift in shaping the genetic diversity in Greenlanders. Based on the mtDNA sequences, the Greenlandic Inuit are phylogenetically close to Siberian groups and Canadian Inuit.